An efficient approach towards review analysis using NLP and Watson - R, Aathira; P. Poonthottam, Viju; ., . (International Journal of Engineering and Technology, 2018)
A large collection of data is available over the internet which can be used to generate the needful relevant information according to individual needs. Even though the information given about an instance is enough to make a summary about it, the opinions and reviews updated by individuals regarding the instance give a clear idea of what the conclusion made by humankind is. So, analyzing reviews by Sentimental analysis help to identify the human opinion about an instance. Along with the reviews, the images uploaded by users showcase the real-time situations without any edits and can lead to a more specific conclusion. Images are analyzed with the tags generated from them using IBM WATSON. Therefore, taking in consideration both images and reviews will generate a well precise report about the instance. The review analysis is done by Naive Bayes Classifier which is considered as the best choice for text classification.Â Â Â